IMPLEMENTASI KEBIJAKAN PENERBANGAN DI BANDAR UDARA WAMENA - Silooy, Telly Nancy (JI@P, 2017)
The aim of the research to analyze the implementation of Aviatiaon Policy involving inter-organization reletionship, characteristics and capability of implementers, organization resources and environment condition. The research was conducted in Jayawijaya Regency. The Method used was descriptive quantitative method. The method of of obtaing the data were questionnire, interview, documentation and observation. The sample consisted of 52 i.e 60 people. The data were analyzed by using frequency table through scale of lickert. Result of research reveal that implementation of aviatian policy in Airport of Wamena does not success well. This is indicated by four independent variables i.e. inter-organization relationship(X1) , characteristics and capability of program implementers (X2), organization resources (X3); environment condition(X4) which is 43,33. To obtain the implementation aviatian policy in airport wamena of Jayawijaya Regency optimally, the government should try more communication consistency and quality by improving knowledge and technicall skill, commitment in porfomming duty, a good control and loyality of target groups and increasing facilities and infrastructures. Key Words : Implementatian, Aviatian, Policy